Overview of sorption analysis capabilities for meso- and microporous zeolites nanomaterials - S. Tokmeilova (Uralʹskij federalʹnyj universitet imeni pervogo Prezidenta Rossii B.N. Elʹcina, 2021)
In this paper we consider the main application features of the thermal desorption method of inert gases, implemented on the Sorbi MS (Meta, Russia) device, for the analysis of meso- and microporous materials. Recommendations on the choice of measurement modes for stable operation of the Sorbi MS device are offered (including recommendations on mass, sample preparation mode). The article presents the results of the micropores analysis by the t-plot and Sing method.